Study of Air and Noise Pollution Due to Transportation in Tarnaka - Rahmat Khan Rahmat; Zabihullah Farkhar; Ahmad Farid Farid; Ahmad Munir Amini; Gulaqa Anwari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
To assess the concentration of carbon monoxide and carbon dioxide, and level of temperature and noise due to transportation vehicles from Secunderabad to Uppal. Road vehicles are primary source of air pollution in urban cities and they also are a considerable source of noise pollution. During this study, pollutants like Carbon monoxide, carbon dioxide were studied besides other parameters like temperature and noise levels were studied for a period of seven days, that is five working and two nonworking days’ from 4th of March till 10th of March 2018, at different time intervals in one of the busiest routes of Hyderabad. The area selected for the study stretches from Secundrabad Railway Station to Uppal Ring Road with ten sampling points. Relative frequency distribution and cumulative relative frequency distribution are used for assessing noise, temperature, CO and CO2 levels. The results of this study identify the status of carbon monoxide, carbon dioxide, and noise pollution. During these days and these different sampling locations, I could come to a conclusion that maximum CO is 12 PPM, CO2 887 PPM, temperature 41℃ and noise is 78 decibels. The study concludes with suggestions for control of air pollution and noise pollution to avoid any health-related issues